Gold endowment of the metasomatized lithospheric mantle for giant gold deposits: Insights from lamprophyre dykes. (1st January 2022) - Wang, Xiang; Wang, Zaicong; Cheng, Huai; Zong, Keqing; Wang, Christina Yan; Ma, Liang; Cai, Ya-Chun; Foley, Stephen; Hu, Zhaochu
Abstract: The metasomatized sub-continental lithospheric mantle (SCLM) is increasingly proposed to play a key control in the formation of giant gold (Au) deposits. However, the extent of Au enrichment in metasomatized SCLM and the Au contents of its derivative partial melts remain poorly constrained. Lamprophyres are derived from low-degree melting of metasomatic and fusible components in the SCLM, and could provide fundamental information about the metasomatized source and metal release compared to mantle peridotites and/or pyroxenites. The giant Jiaodong Au province (> 5000 tons, ∼ 120 Ma) in the eastern part of the North China Craton (NCC) is an ideal locality to assess the Au endowment of metasomatized SCLM which may serve as the source of Au, as indicated by the presence of mantle-dominated volatiles in auriferous fluids associated with the deposits. Based on detailed petrological studies, we analyzed Au, S, Cu and platinum-group element (PGE) contents of the SCLM-derived lamprophyres that are temporally (130–121 Ma) and spatially associated with the Jiaodong lode Au deposits. The lamprophyre dykes were emplaced in the deep crust and did not experience significant degassing and sulfide segregation, and the sulfide saturation occurred at a late stage during magma cooling, as demonstrated by sulfide petrography, S contents, Cu/S and Cu/Pd ratios of the lamprophyres. The relatively oxidized (ΔFMQ +1 – +2), hydrous (2–4 wt.% H2 O) lamprophyres display variable and generally low Au contents (0.04–3.59 ng/g, mainly 1–3 ng/g, n = 31), as well as low PGE and Cu contents. Their high Au/Cu(N) and Au/Pd(N) ratios together with high Ba/Nb indicate a discernible Au addition to their source, resulting from multi-stage mantle metasomatism related to subduction. However, the average Au contents of the metasomatized SCLM before large-scale Au mineralization are heterogeneous and overall in a range of 0.5–1.5 ng/g. The values are higher than that of depleted SCLM (< 0.5 ng/g) but are still lower than or similar to the fertile upper mantle (1.2–1.7 ng/g). These results indicate that mantle metasomatism related to subduction replenished some amount of Au into previously depleted SCLM, leading to local or regional Au enrichment. However, such processes evidently did not result in remarkable Au enrichment of the mantle source beneath the eastern part of the NCC. We thus propose that the metasomatized SCLM and magmas derived from it, though without anomalously high Au contents, could still provide large amounts of Au for large-scale Au mineralization. Importantly, metasomatic volatiles from the metasomatized SCLM exert a key role, and they enable efficient release of Au from mantle sources, promote Au transportation along trans-lithospheric fault channels and subsequent enrichment and precipitation via magmatic-hydrothermal processes for giant Au deposits.